2015
DOI: 10.3390/su7010916
|View full text |Cite
|
Sign up to set email alerts
|

Urban and Rural MSW Stream Characterization for Separate Collection Improvement

Abstract: Abstract:In the new legislation framework enacted by new member countries of the European Union (EU), the characterization of municipal solid waste (MSW) represents an important instrument for local governments and sanitation operators in setting and achieving targets for waste recycling and recovery. This paper presents the results of a study conducted in accordance with the Romanian methodology for domestic wastes characterization ROMECOM, aiming to provide a proper basis for developing clear and realistic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 33 publications
1
34
0
1
Order By: Relevance
“…These occur mainly from non-household sources such as logging activities and flash floods of small catchment areas of Bistrita tributaries. Wood waste, as a fraction of household waste in rural communities, is insignificant (1%) because it is reused as solid fuel [27]. These results point out that rural localities may not be solely responsible for the waste dumping issue.…”
Section: Waste Management Background In the Study Areamentioning
confidence: 64%
See 1 more Smart Citation
“…These occur mainly from non-household sources such as logging activities and flash floods of small catchment areas of Bistrita tributaries. Wood waste, as a fraction of household waste in rural communities, is insignificant (1%) because it is reused as solid fuel [27]. These results point out that rural localities may not be solely responsible for the waste dumping issue.…”
Section: Waste Management Background In the Study Areamentioning
confidence: 64%
“…In this context, a factor of 0.7 is used for measuring the biowaste losses via unsound waste management practices as a realistic scenario [25]. Organic waste may represent 90% of the domestic waste generation rate in remote rural communities, which is mostly used to feed animals and for composting activities [26], but in Romania, this fraction varies from 47-70% across development regions [27]. The Polish National waste management plan [28] assumes that 70% of biodegradable waste generated in villages and 15% of such waste in minor towns is used for the purposes of composting, feeding animals and in household furnaces.…”
Section: Quantification Of Uncontrolled Rural Household Waste Disposalmentioning
confidence: 99%
“…In these context, studies have identified three individuals' indicators [22][23][24][25][26][27][28][29][30]:…”
Section: Role Of Energy Recovery From Msw In a Frame Of Materials Recomentioning
confidence: 99%
“…The regional waste composition data (2003) provided by regional waste management plans (2006) are specific to rural areas based on local waste operators estimations. Ciuta et al (2015) performed experimental studies for Sercaia commune (Brasov county, Center Region), but the municipal waste composition data computed are specific only for regional level. Such data are not broken down into urban and rural areas as per-capita waste generation rates.…”
Section: Estimations Of Biowaste Generated and Uncollectedmentioning
confidence: 99%
“…These calculations are determined based on rural population unserved (nr.of inhabitants) by waste collection services (WCS) and on the other hand, by rural municipal waste composition at NUTS 2 scale (nomenclature of territorial units for statistic: http://ec.europa.eu/eurostat/web/nuts/overview) provided by regional waste management plans for 2003 andCiuta et al(2015) for 2012. The amounts of bio-waste generated and uncollected is determined as: Q bwu (t.yr -1 )= P noWCS * G rw *365/1000 * S bwr (%) where:  Q bwu = amount of biowaste generated and uncollected by waste operators (t.yr -1 )…”
Section: Estimations Of Biowaste Generated and Uncollectedmentioning
confidence: 99%